Antimicrobial resistance and genomic investigation of Salmonella isolated from retail foods in Guizhou, China - Zhou, Li; Ye, Qian; Zhou, Qian; Wang, Jian; Li, Guanqiao; Xiang, Jingshu; Huang, Jingyu; Zhao, Yuanyuan; Zheng, Tianli; Zuo, Haojiang; Li, Shijun (Frontiers in Microbiology, 2024)
Salmonella is a major foodborne pathogen worldwide that causes severe morbidity and mortality. It is mainly caused by consuming contaminated food, with retail food considered the primary source. In Guizhou, China, 102 Salmonella strains isolated from 2016 to 2021 underwent phenotypic antimicrobial resistance testing and whole-genome sequencing (WGS) to understand Salmonella diversity, including serotypes, sequencing types (STs), antimicrobial genes, virulence genes, plasmid types, multi-locus sequence types (MLST), and core genome MLST (cgMLST). S.Typhimurium was the dominant serotype, and O:4(B) was the leading serogroup. The most prevalent genotype was ST40. Phenotypic antimicrobial resistance identified 66.7% of the sampled isolates as multi-drug resistant (MDR). S.Enteritidis (n=7), S.Typhimurium (n=1), S.Indiana (n=1), S.Kentucky (n=1), S.Uganda (n=1), all of which were MDR, were resistant to Colistin. Resistance rates varied significantly across different strains and food types, particularly meat products exhibiting higher resistance. Notably, significant increases in resistance were observed from 2016 to 2021 for the following: ≥1 resistant (P=0.001), MDR (P=0.001), ampicillin (P=0.001), tetracycline (P<0.001), chloramphenicol (P =0.030), and trimethoprim/sulfamethoxazole (P=0.003). The marked escalation in drug resistance over the recent years, coupled with the varying resistance rates among food sources, underscores the growing public health concern. Our findings highlight the need for a coordinated approach to effectively monitor and respond to Salmonella infections in Guizhou, China.